Fiction’s Afterlives: Character Migration and Reading Memory - Ivan CALLUS (E-REA)
The migration of characters across literary and paraliterary texts is quite routinely discussed in theories of intertextuality, in postmodernist poetics, and in the critical discourse surrounding transmedia. This paper, conversely, looks at characters who fail to effect any migration and who fall away from reading memory (both individual and collective). Drawing in particular on the fortunes of Walter Scott and his different literary posterities, and with reference also to related points that emerge in the work of poets from Wordsworth to Alice Oswald and novelists from Henry James to Howard Jacobson, it reflects on the relevance of a concern with literary character in an age dominated by talk about avatars and digital platforms. Reference is also made to relevant criticism in the work of critics like Jerome McGann, Catherine Belsey, and others, in an effort to bring together questions concerning reading memory, literary character, and fictions’ afterlives.